2016
DOI: 10.5194/hess-20-175-2016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing various drought indicators in representing summer drought in boreal forests in Finland

Abstract: Droughts can have an impact on forest functioning and production, and even lead to tree mortality. However, drought is an elusive phenomenon that is difficult to quantify and define universally. In this study, we assessed the performance of a set of indicators that have been used to describe drought conditions in the summer months (June, July, August) over a 30-year period (1981-2010) in Finland. Those indicators include the Standardized Precipitation Index (SPI), the Standardized Precipitation-Evapotranspirat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 61 publications
0
40
0
Order By: Relevance
“…The Northern Hemisphere boreal forests usually grow in areas of excessive moisture and tree roots are deeper, so they react much slower to the precipitation deficit (such deficit may even lead to higher VCI values). Also, due to the high initial soil moisture, the drought impact on forested areas can be minimal (Gao et al, 2016). Only during the prolonged extreme droughts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The Northern Hemisphere boreal forests usually grow in areas of excessive moisture and tree roots are deeper, so they react much slower to the precipitation deficit (such deficit may even lead to higher VCI values). Also, due to the high initial soil moisture, the drought impact on forested areas can be minimal (Gao et al, 2016). Only during the prolonged extreme droughts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A five-layer soil hydrology scheme was implemented in JS-BACH by Hagemann and Stacke (2015). Gao et al (2016) has demonstrated that JSBACH with its five-layer soil hydrology scheme is able to capture the soil moisture dynamics at sites and on the regional scale of Finland.…”
Section: Jsbach Land Surface Modelmentioning
confidence: 99%
“…In this study, the soil moisture dynamics are represented by SMI (also referred to as Relative Extractable Water -REW), which has been demonstrated to represent summer drought in boreal forests in Finland (Gao et al, 2016). The SMI describes the ratio of plant available soil moisture to the maximum volume of water available to plants in the soil (Betts, 2004;Seneviratne et al, 2010):…”
Section: Soil Moisture Index (Smi)mentioning
confidence: 99%
See 2 more Smart Citations